2017
DOI: 10.1111/tra.12504
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in kinesin function

Abstract: The kinesin family proteins are often studied as prototypical molecular motors; a deeper understanding of them can illuminate regulation of intracellular transport. It is typically assumed that they function identically. Here we find that this assumption of homogeneous function appears incorrect: variation among motors' velocities in vivo and in vitro is larger than the stochastic variation expected for an ensemble of "identical" motors. When moving on microtubules, slow and fast motors are persistently slow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…2 c ). Previous work demonstrated that different kinesins can have different velocities 23 , but our prolonged observations showed that even individual kinesins undergo considerable velocity fluctuations over time.…”
Section: Resultsmentioning
confidence: 55%
“…2 c ). Previous work demonstrated that different kinesins can have different velocities 23 , but our prolonged observations showed that even individual kinesins undergo considerable velocity fluctuations over time.…”
Section: Resultsmentioning
confidence: 55%
“…2 c ). Previous work demonstrated that different kinesins can have different velocities 21 , but our prolonged observations showed that even individual kinesins undergo considerable velocity fluctuations over time.…”
Section: Resultsmentioning
confidence: 55%
“…Heterogeneity in single-kinesin velocity has been previously observed for the same motor construct. 46,47 Here, we found that the fraction of slow runs increased substantially as the density of motors on the cargo increased. For example, at a motile fraction of 0.8, 56% of cargos moved slower than 0.6 µm/s [ Fig.…”
Section: Membrane-enclosed Cargos Move Faster Than Membrane-free Cmentioning
confidence: 65%
“…The velocity of a single motor is not typically uniform within a population of kinesins. 46,47 During transport by a small team of kinesins, the faster motors lead the cargo and the slower motors lag behind; forcebased interactions between motors tend to prompt the lagging kinesin to dissociate prematurely from the microtubule, 6 causing the cargo to tumble forward to the position of the leading motor. Sliding of motors within the lipid membrane delays force-based interactions between motors and enables the leading kinesin to move forward further before the lagging motor dissociates.…”
Section: Membrane-enclosed Cargos Move Faster Than Membrane-free Cmentioning
confidence: 99%